A panel of glycoproteins as candidate biomarkers for early diagnosis and treatment evaluation of B-cell acute lymphoblastic leukemia. Issue 1 (December 2016) - Cavalcante, Marcio de Souza; Torres-Romero, José; Lobo, Marina; Moreno, Frederico; Bezerra, Leonardo; Lima, Diego; Matos, Jesamar; Moreira, Renato de Azevedo; Monteiro-Moreira, Ana
Abstract Background Acute lymphoblastic leukemia is the most common malignant cancer in childhood. The signs and symptoms of childhood cancer are difficult to recognize, as it is not the first diagnosis to be considered for nonspecific complaints, leading to potential uncertainty in diagnosis. The aim of this study was to perform proteomic analysis of serum from pediatric patients with B-cell acute lymphoblastic leukemia (B-ALL) to identify candidate biomarker proteins, for use in early diagnosis and evaluation of treatment. Methods Serum samples were obtained from ten patients at the time of diagnosis (B-ALL group) and after induction therapy (AIT group). Sera from healthy children were used as controls (Control group). The samples were subjected to immunodepletion, affinity chromatography with α-d -galactose-binding lectin (fromArtocarpus incisa seeds) immobilized on a SepharoseTM 4B gel, concentration, and digestion for subsequent analysis with nano-UPLCtandem nano-ESI-MSE . The programExpression E was used to quantify differences in protein expression between groups. Results A total of 96 proteins were identified. Leucine-rich alpha-2-glycoprotein 1 (LRG1), Clusterin (CLU), thrombin (F2), heparin cofactor II (SERPIND1), alpha-2-macroglobulin (A2M), alpha-2-antiplasmin (SERPINF2), Alpha-1 antitrypsin (SERPINA1), Complement factor B (CFB) and Complement C3 (C3) were identified as candidate biomarkers for early diagnosis of B-ALL, as they were upregulated in the B-ALL group relative to the control and AIT groups. Expression levels of the candidate biomarkers did not differ significantly between the AIT and control groups, providing further evidence that the candidate biomarkers are present only in the disease state, as all patients achieved complete remission after treatment. Conclusion A panel of protein biomarker candidates has been developed for pre-diagnosis of B-ALL and also provided information that would indicate a favorable response to treatment after induction therapy.